Prediction of Consumer Repurchase Intention with Food Delivery Apps: The Mediating Role of Prior Online Experience Using PLS-SEM-ANN Approach - Herzallah F. (Springer Science and Business Media Deutschland GmbH, 2024)
The snowballing approval of food delivery apps (FDAs) in developing countries, including Palestine, calls for a deep insight into this trait. However, limited research has been conducted in Palestine regarding the acceptance and usage of FDAs. Addressing this research gap, this study examines the mediating role of prior online experience (POE) in the relationship between UTAUT2 constructs performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivations and consumer repurchase intention (RI) from FDAs. With collecting a sample of 392 customers, a two-step hybrid approach is employed, utilizing partial least squares structural equation modelling (PLS-SEM) for testing hypotheses and artificial neural networks (ANN) for assessing the significance of the construct. The results confirm all hypotheses, indicating that UTAUT2 constructs positively influence POE. Furthermore, POE significantly affects RI, acting as a mediator between UTAUT2 constructs and RI. The analysis of the ANN demonstrates that effort expectancy and facilitating conditions are the most influential factors on POE, while social influence shows relatively lower importance. This research contributes to raise awareness of FDA adoption and usage patterns in developing countries, providing valuable insights for policymakers, businesses, and consumers. The findings emphasize the crucial role of POE in shaping consumers RI from FDAs. The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.